Measures for Reducing Traffic Congestion in Cities - Dadić, Ivan; Kos, Goran; Poić, Krešimir; Gašparac, Emil (Promet - Traffic&Transportation, 2012)
Traffic planners and designers are daily confronted by theproblems of traffic flow. Finding a solution for the optimal organisationof the traffic system in the wider (at the state level)and the narrower sense (cities, towns), requires accurate planningand adequate financing. With Croatia being a developingcountry that has higher investments into the traffic system, thematerial means need to be rati01 t lised and the human andland resources cautiously managed. With the development andimplementation of the traffic studies, an improvement of thetraffic in cities can be expected. The work describes the trafficmeasures which provide higher quality traffic flow, with low investments.They can be used as guidelines in planning the trafficand as the first implementations of solutions from the trafficstudies.